Transferring neurointerventionalists saves time compared with interhospital transfer of stroke patients for endovascular thrombectomy: a collaborative pooled analysis of 1001 patients (EVEREST) - Seker, Fatih; Fifi, Johanna T.; Morey, Jacob R.; Osanai, Toshiya; Oki, Sogo; Brekenfeld, Caspar; Fiehler, Jens; Bendszus, Martin; Möhlenbruch, Markus Alfred (Journal of neuroInterventional surgery, 2023)
Background Interhospital transfer of stroke patients (drip and ship concept) is associated with longer treatment times compared with primary admission to a comprehensive stroke center (mothership concept). In recent years, studies on a novel concept of performing endovascular thrombectomy (EVT) at external hospitals (EXT) by transferring neurointerventionalists, instead of patients, have been published. This collaborative study aimed at answering the question of whether EXT saves time in the workflow of acute stroke treatment across various geographical regions. - Methods This was a patient level pooled analysis of one prospective observational study and four retrospective cohort studies, the EVEREST collaboration (EndoVascular thrombEctomy at Referring and External STroke centers). Time from initial stroke imaging to EVT (vascular puncture) was compared in mothership, drip and ship, and EXT concepts. - Results In total, 1001 stroke patients from various geographical regions who underwent EVT due to large vessel occlusion were included. These were divided into mothership (n=162, 16.2%), drip and ship (n=458, 45.8%), and EXT (n=381, 38.1%) cohorts. The median time periods from onset to EVT (195 min vs 320 min, p<0.001) and from imaging to EVT (97 min vs 184 min, p<0.001) in EXT were significantly shorter than for drip and ship thrombectomy concept. - Conclusions This pooled analysis of the EVEREST collaboration adds evidence that performing EVT at external hospitals can save time compared with drip and ship across various geographical regions. We encourage conducting randomized controlled trials comparing both triage concepts.